2020
DOI: 10.1063/5.0027022
|View full text |Cite
|
Sign up to set email alerts
|

Emerging applications at the interface of DNA nanotechnology and cellular membranes: Perspectives from biology, engineering, and physics

Abstract: DNA nanotechnology has proven exceptionally apt at probing and manipulating biological environments as it can create nanostructures of almost arbitrary shape that permit countless types of modifications, all while being inherently biocompatible. Emergent areas of particular interest are applications involving cellular membranes, but to fully explore the range of possibilities requires interdisciplinary knowledge of DNA nanotechnology, cell and membrane biology, and biophysics. In this review, we aim for a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 211 publications
0
31
0
Order By: Relevance
“…DNA origami has emerged as a powerful nanotechnology platform for sensing and modulating cellular activities. ,,,, It is therefore of particular interest to target DNA origami nanostructures directly to the cell surface. Cholesterol labeling has been commonly used for achieving such a purpose, , which directs origami nanostructures to the phospholipid bilayer (PLB).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA origami has emerged as a powerful nanotechnology platform for sensing and modulating cellular activities. ,,,, It is therefore of particular interest to target DNA origami nanostructures directly to the cell surface. Cholesterol labeling has been commonly used for achieving such a purpose, , which directs origami nanostructures to the phospholipid bilayer (PLB).…”
Section: Resultsmentioning
confidence: 99%
“…The DNA origami forms 2D and 3D nanostructures from the self-assembly of approximately 200 short single-stranded DNA (ssDNA), referred to as “staple strands”, based on a large ssDNA scaffold. Formation of the DNA origami allows highly predictable and reproducible assembly of biocompatible structures at the nanoscale and offers convenience for the incorporation of probe labeling (fluorescence and non-fluorescence) and sequence-selective targeting. With the capacity to carry a range of functionalities, DNA origami becomes a desirable candidate for assessing glycocalyx structures with thicknesses up to a few hundred nanometers …”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrated that the addition of the surfactant can facilitate DNA constructs' membrane spanning. Although not suitable for in vivo applications, this will provide new perspectives for nanopore use, including DNA and protein sequencing [27,49,51,52], and will enable the modeling and fine-tuning of the designs of DNA-based components of synthetic cells, such as membrane enzymes or ion channels [1,53,54]. Our findings shed light on the DNA membrane insertion issue, particularly by showing the importance of aggregation in membrane activity and helping to more deeply understand the action of surfactants in the DNA-lipid system.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially important for therapeutic applications such as DNA-based drug delivery systems; hence, building a stable structure has been a target property in design [90], [91]. Yet, it is hard to find a proper design strategy against this problem other than decorating with other molecules to prevent digestion or bolstering the rigidity of the structure overall since there is various uncertainties in factors affecting the stability [24], [27], [92]. As a result, computational models that consider this issue in the design phase are hardly found.…”
Section: Multiscale Characteristics Of the Mechanical Properties In D...mentioning
confidence: 99%